Community-Based Da’wah through Children’s Religious Education in the Digital Age: A Study of the Rumah Cita Program in Pekanbaru - Muhlasin, Muhlasin; Khair, Latiful; Pramana, M Agung (Institut Agama Islam Sunan Giri Ponorogo, 2025)
The pervasive use of digital devices has precipitated moral and ethical challenges among children, necessitating innovative da'wah approaches beyond formal educational institutions. While contemporary scholarship has extensively examined institutionalized Islamic education, the theoretical integration of secular basic literacy and religious instruction as a community-based da'wah medium remains underexplored. This study addresses this gap by investigating how the Rumah Cita program, initiated by the Seribu Satu Cita Foundation in Pekanbaru, reconfigures da'wah pedagogy. Employing a theoretical framework based on the core elements of da'wah (da'i, mad'u, maudu', uslub, and wasilah) synthesized with the concept of tarbiyah (continuous Islamic education), this qualitative case study utilized in-depth interviews and participant observation. Thematic analysis reveals that the program transcends traditional religious knowledge transfer. Specifically, it conceptualizes basic literacy (reading and writing) as a fundamental wasilah (medium) of da'wah, empowering the mad'u (children) to access Islamic teachings. Furthermore, the instruction of theology and morality (akidah akhlak) and prophetic storytelling (kisah nabi) are deployed as a strategic uslub (method) grounded in uswatun hasanah (exemplary character) to counteract the degradation of manners (adab) caused by technological exposure. This article contributes to contemporary da'wah studies by providing a theoretical justification that basic literacy instruction, when integrated with a moral curriculum, operates as a transformative act of da'wah.